A support approach for the modular design of Li-ion batteries: A test case with PCM. (October 2020) - Cicconi, Paolo; Kumar, Pradeep; Varshney, Peeyush
Highlights: A modular approach to support the design of Li-ion batteries. The case study describes a battery module with Li-ion cells type 18650. Simulations and the design approach are focused on one battery module. The modularity is extended to the layout of the cooling system. The cooling system consists of a passive PCM and an air-cooling system. ABSTRACT: Nowadays, there is an increasing interest in Phase-Change Materials due to their capacity to store latent heat during the phase transition. In the literature, the solid-liquid change is widely applied in cooling applications such as the thermal management of Li-ion batteries. The optimization of the cooling system is one of the solutions to reduce battery aging and increase the battery lifetime. Even if Phase-Change Materials are studied to be used in this context, there is still a lack of suitable solutions to be used in engineering design for a further product commercialization. In this context, the paper proposes a modular approach to support the design of a battery pack considering Phase-Change Materials in the cooling system. The approach shows how a single module of cells can be stacked and how the cooling system of each module can be easily connected to each other. The modularity concept is extended from the electrical configuration to the cooling system. As a test case, a battery module has been analyzed. The battery module has been simulated using a Computer-Aided Engineering tool to analyze the behavior of the temperature profile under loading conditions. Graphical abstract: Image, graphical abstract